2013
DOI: 10.2175/106143013x13596524516220
|View full text |Cite
|
Sign up to set email alerts
|

Foaming Phenomenon in Bench‐Scale Anaerobic Digesters

Abstract: The Madison Metropolitan Sewerage District (The District) in Madison, Wisconsin has been experiencing seasonal foaming in their anaerobic biosolids digesters, which has occurred from mid‐November to late June for the past few years. The exact cause(s) of foaming is unknown. Previous research findings are unclear as to whether applications of advanced anaerobic digestion processes reduce the foaming potential of digesters. The object of this study was to investigate how configurations of thermophilic and acid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Similar results have been observed in other plants as well (Jenkins et al, 2003;Pagilla et al, 1998). It has been hypothesized that this is because the hydrophobic cell walls cause foaming in anaerobic digesters and destroying the cells only disperses them more evenly throughout the digester (Jenkins et al, 2003;Siebels and Long, 2012). Although PAX-14 has been shown to limit the growth of Microthrix parvicella in aeration basins, it also traps the organism in more dense flocs, which results in many of the organisms that would ordinarily be collected by scum skimmers instead ending up in the anaerobic digesters.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Similar results have been observed in other plants as well (Jenkins et al, 2003;Pagilla et al, 1998). It has been hypothesized that this is because the hydrophobic cell walls cause foaming in anaerobic digesters and destroying the cells only disperses them more evenly throughout the digester (Jenkins et al, 2003;Siebels and Long, 2012). Although PAX-14 has been shown to limit the growth of Microthrix parvicella in aeration basins, it also traps the organism in more dense flocs, which results in many of the organisms that would ordinarily be collected by scum skimmers instead ending up in the anaerobic digesters.…”
supporting
confidence: 75%
“…The primary purpose of this study was to determine if adding PAX to an activated sludge aeration basin would reduce foaming in the subsequent anaerobic digester receiving the PAX-containing WAS. In this study, PAX-18 (18% aluminum oxide content) was tested based on the recommendations of the manufacturer (Kemira, Atlanta, GA), Previous work using solids from the studied plant has indicated that non-viable organisms contribute to foaming in anaerobic digesters, and breaking the cells apart may actually increase foaming issues (Siebels and Long, 2012). Similar results have been observed in other plants as well (Jenkins et al, 2003;Pagilla et al, 1998).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Foaming potential was measured using a similar approach to others (Ross & Ellis, 1992;Siebels & Long, 2013). A 100 ml sample of digestate was placed in a 1000-ml graduated cylinder with an aeration stone placed at the bottom of the graduated cylinder.…”
Section: Cod Mass Balancementioning
confidence: 99%
“…Alkalinity was a critical parameter in the digestion of thin stillage (Alkan-Ozkaynak and Karthikeyan, 2011). Foaming in different waste streams was assessed by Siebels and Long (2011), and bench-scale and acid-phase thermophilic treatment processes had a higher foaming potential than bench-scale mesophilic digestion. Shimada et al (2011b) assessed a two-phase acid-methane anaerobic digester to understand what bacteriological processes predominated, and found that the acid stage inhibited aceticlastic methanogens, and…”
Section: Coupled Systemsmentioning
confidence: 99%